Crude glycerol to valuable chemical product- a reliable industry process - Mohd Hasbi, Ab. Rahim; Paroo Indran, Vidhyaa; Anisah Sajidah, Haji Saud; Mior Ahmad Khushairi, Mohd Zahari; Gaanty Pragas, Maniam (2018)
Market of organic carbonates chemical is dominated by petroleum-based products. Under-utilized crude glycerol for the production of valuable high end products. Inability to directly utilised crude glycerol hinders the growth of existing technology.